Assessment of the minimal available phosphorus needs of laying hens: Implications for phosphorus management strategies. (22nd June 2018) - Jing, M; Zhao, S; Rogiewicz, A; Slominski, B A; House, J D
ABSTRACT: The oversupply of dietary phosphorus (P) leads to increased feed costs and discharge of excessive P to the environment, thus directly impacting the sustainability of egg production practices. The present study was conducted to better define the minimal available P needs of laying hens. Fifty-six Lohmann white laying hens were individually caged and fed one of 7 diets with graded levels of available P (0.15, 0.20, 0.25, 0.30, 0.35, 0.40, or 0.45%) for 12 weeks. Records were maintained for body weight, feed intake, and egg production during the experimental period. Blood and egg samples were collected and digestibility studies conducted at wk 6 and 12 of the experiment. At the end of the experiment, tibia characteristics and expression of the P transporters in the small intestine and kidney were determined. Lowering dietary available P from 0.45 to 0.15% generally reduced plasma P concentrations ( P < 0.01), but hen productive performance, plasma calcium, parathyroid hormone and other constituents, tibia bone mineral density and content, tibia ash percentage, and mRNA abundance of the small intestine, and kidney type II sodium/phosphate cotransporter were not different among treatments. Specific gravity and eggshell thickness tended to increase with reducing dietary P ( P < 0.05). Total P intake, excretion, and retention net amount decreased ( P < 0.01) with reducing dietary P, but its retention rate (of intake) remained unchanged. Furthermore, changing dietary P did not affect calcium retention rate and net deposition of total P and calcium in eggs. These data indicate that reducing dietary available P up to 0.15% is adequate to maintain health and performance of layers. As such, this minimal available P estimate should serve as a benchmark for the assessment of P contents of commercial laying hen rations, with the goal of enhancing the sustainability of egg production.